The Internationalisation Process of an E-Commerce Entrepreneurial Firm: The Inward-Outward Internationalisation and the Development of Knowledge - Magdalena Grochal-Brejdak; Maja Szymura-Tyc (Entrepreneurial Business and Economics Review)
Objective: The article aims at the description of the internationalisation process of an entrepreneurial e-commerce trading firm, depicting the course and mechanism of the process.